Frequency Diverse Array Antennas: From Their Origin to Their Application in Wireless Communication Systems - Nusenu, Shaddrack Yaw; Basit, Abdul (Journal of Computer Networks and Communications, 2018)
Wireless communication systems have gained considerable growth rate nowadays, with the anticipation that communications will be available everywhere and anywhere in the near future. Phased array antenna whose beam steering is fixed in an angle for all range cells has been utilized for wireless communications. To mitigate this problem, a new array concept, namely, frequency diverse array (FDA), was proposed. This paper presents how FDA technology could be useful in today’s wireless communication technology. FDA is distinct from phased array in a sense that it employs frequency increment across array elements. The use of a frequency increment creates a beam steering that is a function of angle, time, and range which allows the FDA antenna to transmit the energy along the prespecified range and angle direction. In addition, we consider the time-variant beampattern aspect of an FDA, which has normally been ignored in the literature. In this study, we present the mathematical fundamentals of FDA antenna and why it could be exploited for wireless communication systems. Furthermore, FDA using Butler matrix for communication has been discussed. Performance analysis in terms of transmit beampattern, signal-to-interference-and-noise ratio (SINR), and direction of arrival has been presented and compared with that of phased array antenna.